Squaring the Circle Using Modified Tartaglia Method - Szyszkowicz, Mieczysław (Trends in Computer Science and Information Technology, 2016)
The paper presents a modified Tartaglia method. Tartaglia proposed a simple approach to perform an approximate quadrature of the circle. His construction results with the number pi=3.125. Using a similar construction as Tartaglia but with different proportions improves the accuracy of his method.